2019
DOI: 10.1161/circresaha.118.313563
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Heart of Alzheimer Disease

Abstract: In a somewhat narrow diagnostic lens, Alzheimer’s Disease (AD) has been considered a brain specific disease characterized by the presence of β-Amyloid plaques and tau neural fibrillary tangles and neural inflammation; these pathologies lead to neuronal death and consequently clinical symptoms such as memory loss, confusion, and impaired cognitive function. However, for decades researchers have noticed a link between various cardiovascular abnormalities and AD - such as heart failure (HF), coronary artery disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 81 publications
(108 reference statements)
2
104
0
Order By: Relevance
“…The majority of these genes are known to participate in amyloid plaque formation and neurodegenerative disorders. Our novel network points towards a previously emerged link between cardiovascular disease and Alzheimer’s disease [ 54 ]. Indeed, Alzheimer’s disease revealed one of the highest betweenness in our multi-integration approach.…”
Section: Discussionmentioning
confidence: 88%
“…The majority of these genes are known to participate in amyloid plaque formation and neurodegenerative disorders. Our novel network points towards a previously emerged link between cardiovascular disease and Alzheimer’s disease [ 54 ]. Indeed, Alzheimer’s disease revealed one of the highest betweenness in our multi-integration approach.…”
Section: Discussionmentioning
confidence: 88%
“…Importantly, abnormal protein oligomers/aggregates have been reported to disturb Ca 2+ homeostasis and contribute to the cardiac pathology [90]. Thus, the common regulatory mechanism behind the convergence between AD and cardiac diseases could be the Ca 2+ dysfunction [87] but the field is open to new hypotheses [91].…”
Section: Presenilinsmentioning
confidence: 99%
“…Alzheimer disease is a brain-speci ic disorder characterized by the presence of tau NFT, neural in lammation, and Aβ plaques [51][52][53]. These pathologies cause neuronal death and concomitant clinical symptoms, such as confusion, impaired cognitive function, and memory loss [54][55][56]. One of the key characteristics of AD is the substantial and progressive erosion of neurons in the cortex [57].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…An imbalance between ROS production and the activities of enzymes responsible for ROS scavenging results in increased oxidative damage in AD patients [54]. Numerous studies have demonstrated that OS and ROS have a signi icant role in AD by causing deleterious effects to proteins and other important biomolecules [20,60].…”
Section: Alzheimer's Disease and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation